Performance Appraisal Purpose and Job Embeddedness: Examining the Interaction Effect of Multidimensional Locus of Control - Naeem, Muhammad; Shah, Dr. Fayaz Ali; Kakakhel, Dr. Shahid Jan (The journal of contemporary issues in business and government, 2021)
Using Social exchange theory, this study aimed to examine whether the developmental and evaluative purpose of performance appraisal significantly predicts job embeddedness and the interaction effect of internal and external locus of control. Data were gathered from salespersons of the pharmaceutical industry working in Peshawar, Khyber Pakhtunkhwa. A sample of 304 respondents using a cross-sectional survey was drawn for final analysis using non-probability sampling technique. Measurement and structural model was tested using partial least squares structural equation modeling (PLS-SEM). Findings revealed that both developmental performance appraisal and evaluative performance appraisal significantly and positively influence job embeddedness. Results also indicate that internal and external locus of control significantly moderates the relationship between developmental and evaluative performance appraisal with job embeddedness. These findings provide important insights in understanding the dimensions of performance appraisal for predicting workplace outcome. The study has theoretically contributed to the existing literature by examining the boundary condition of internal and external locus of control. Finally, recommendations for managers and future research directions have been documented at the end of the study.